A Application of G. Polya’s Problem-Solving Process in Teaching High-School Physics - Le Chi Nguyen; Hoang Trung Thuan; Ta Thi Huong Giang (Journal La Sociale, 2023)
The study investigates the application of G. Polya’s four-step problem-solving process in teaching Physics. This teaching method helps students form and develop problem-solving skills in learning, including (1) Understanding the problem; (2) Making a plan; (3) Executing the plan; (4) Looking back and reflecting. An experimental teaching session on “some forces in practice” for 300 tenth graders in two high schools (grade 10) was conducted as part of this study. Experimental results at first show that more than 80% of students have significantly improved their problem-solving skills. These experimental results are expected to enable teachers and students to teach and learn Physics effectively, meeting the expected outcomes of the General Education Program.